Political parties in Palestine leadership and thought - Bröning, Michael; Judith Althaus; Usama Anthar; Stefanie kirster; Helene Kortlander; Henrik Meyer; Alexander Rusche; Eva Schreiner (Palgrave Macmillan, 2013)
"Political Parties in Palestine is an up-to-date elucidation of the Palestinian political landscape. The book offers vital background information on movements such as Hamas and Fatah, as well as smaller political factions that have defined the Israeli-Palestinian conflict for decades but, due to lack of available information, have not been subject to academic scrutiny.The book provides a comprehensive discussion of the ideological outlook, historical development, and political objectives of all major political actors in the Palestinian Legislative Council (PLC). A well-informed but accessible overview, it combines analytical introductions with engaging profiles of party founders, interviews with current party leaders, organizational charts, and excerpts from party programs previously unavailable in English"-- c Provided by publisher